Adaptation and validation of the Brazilian Portuguese version of the Leader Empowering Behavior scale - Guerra Mutro, Maria Eugenia [UNESP]; Spiri, Wilza Carla [UNESP]; Monti Juliani, Carmen Maria Casquel [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP]; Bernardes, Andrea; Trettene, Armando dos Santos (Assoc Brasileira Enfermagem, 2020)
Objectives: to adapt and validate the Leader Empowering Behaviorscale for Brazilian Portuguese in a sample of Brazilian nurses. Methods: cross-sectional study through translation, back-translation, expert evaluation, application and analysis of content, criteria and construct of the scale. Results: the title of the final version was Comportamento Empoderador do Lider. The equivalence evaluation presented Content Validity Index of 89% among the 27 items of the original scale and was applied to 272 nurses. For the construct validation, psychometric analyzes were performed; through calculations of the measure of sampling adequacy, were excluded six items from the translated instrument; and in the factor analysis, four factors were retained. The Cronbach's alpha was calculated for the four domains and ranged from 0.82 to 0.87,demonstrating the scale reliability. Conclusions: the adapted version presented validity and reliability criteria for use in Brazil. Its use will make it possible to know the behavior of leaders to empower their team.
Keywords: Validation Studies; Leadership; Professional Practice Management; Power; Nursing Administration Research